Quantum Statistics in Cylindrical Time-evolution of Electrons and Physical Reality - Thuan, Vo Van; Duc, Dao Dinh (VNU Journal of Science: Mathematics - Physics, 2020)
Due to helical cylindrical time-evolution of electrons the mankind observation at a quantum mechanical scale depends on synchronization between observers and their surrounding cosmological medium by collective dynamics. From one side, the synchronization leads to linearization of an embedded 4D space-time reminiscent of the flat Minkowski space-time. From another side, variation of the synchronization due to independent proper plane wave oscillations of each electron being constrained in a short time quantized period, implies that there only statistical averaged physical quantities are observable, which is in consistency with statistical indeterministic concept of traditional quantum mechanics.